A Systematic Scoping Review of the Resilience Intervention Literature for Indigenous Adolescents in CANZUS Nations - Jongen, Crystal Sky; McCalman, Janya; Bainbridge, Roxanne Gwendolyn (Frontiers in Public Health, 2020)
Background: The concept of resilience offers a strengths-based framework for interventions to enhance Indigenous adolescent social and emotional well-being. Resilience interventions in or with schools encompass individual, social, and environmental factors that encourage health-promoting behaviors and assist adolescents in navigating toward resources that can sustain their health and well-being in times of adversity. This scoping review examined the literature on resilience-enhancing interventions for Indigenous adolescent students in Canada, Australia, New Zealand, and the United States (CANZUS nations). Intervention strategies, adherence to theoretical constructs, and outcomes were analyzed. Methods: A systematic search was conducted of intervention studies aimed at improving Indigenous adolescent resilience and published in CANZUS nations between January 1990 and May 2016. Eleven peer-reviewed databases and 11 websites and clearing houses were searched for relevant studies. Following double-blinded screening, a total of 16 intervention papers were included for analysis. Study characteristics were identified and study quality was assessed using appropriate assessment tools. Results: Twelve interventions (75%) were delivered in school settings and four (25%) were community-based, conducted in partnership with schools. Seven publications (44%) reported interventions focused exclusively on fostering individual resilience. Another seven (44%) included components that aimed to build staff, school, and/or community capacity to support adolescent resilience, and two (12.5%) had community/school capacity-building as the primary focus. Culturally based approaches to enhancing resilience were evident in most studies (81%). The publications documented the use of a range of program models, processes, and activities aligned with resilience theory. Positive outcomes were reported for improved individual assets (e.g., strengthened self-esteem and Indigenous identity), environmental resources (e.g., increased peer support and social/community connection), and increased community capacity (e.g., increased youth training and leadership opportunities). On average, study quality was assessed as moderate to high. The strongest evidence of intervention effectiveness was for improvements in mental health symptoms and outcomes. Conclusion: Interventions indicated strong alignment with ecological and culturally based resilience theories and models. While the results of the studies indicate some positive impacts on the resilience of Indigenous adolescents, future evaluations should aim to ensure high study quality and focus on measuring strengths-based resilience outcomes.